Evaluating the maturity level of TQM benefits in Pakistan. (8th October 2019) - Arslan, Muhammad
Previous studies majorly focus on defining TQM and describing relationship between TQM practices and performance. This paper addresses the achievement of post implementation benefits of total quality management (TQM). TQM is highly emphasised from the last decade in industries of Pakistan and this examination shows practical influence after implementation. A survey form was designed and the survey was conducted in diversified type of companies in Pakistan. Analysis through descriptive statistics of 61 survey forms represents that organisations, following TQM approach, are realising the positive paybacks of TQM. Consequently, it is a source of inspiration to help the non-TQM industries to implement TQM and understand the actual performance of TQM system so they can achieve the direct and indirect benefits in terms of profit. One of the firms, before implementing TQM, assigned a project to conduct a practical survey which will contribute to know the extent of the industry practitioners about the maturity level of TQM benefits to compete at global market place. Finally, it aims to provide the idea for any industry to initiate the application of TQM.